SPORT, GENDER DIFFERENCES AND SEXUALITY BETWEEN SOCIAL STEREOTYPES AND EDUCATIONAL NEEDS FOR RECOGNITION OF SUBJECTIVITIES - Antonia CUNTI; Sergio BELLANTONIO; Alessandra PRIORE (Cluj University Press, 2016)
Sport symbolizes a powerful instrument to propagate social stereotypes that feed and exacerbate also gender differences. The discrimination messages about gender are very frequent in sport and most of the time they have not direct and clear appearances, but the signals are implicit, hidden and nonverbal, not for this less effective. The educational instance that emerges strongly is which that consists in supporting individual paths of self-research, which could mean a suffered journey that requires difficult integrations. In light of this, what can be the educability dimension which should be supported by a sport that focuses on the individual's subjectivity, thus also his sexuality? Intending sport in a broader sense, and then considering all forms of organized activity related to movement, it might be appropriate to induce several aspects that may confer to sport an intentional educational value. It is at this point that the pedagogy is called upon to reflect critically on sports situations, to direct actions towards the construction of the learning setting that can promote wellness and well-being of involved persons. On a pedagogical perspective, is worthwhile reflect on how sport can becomes a context able to allow subjects to test themselves freely, even developing abilities and behaviors useful to feed life skills to a harmonious growth with themselves and in their own living environments. A sport supporter of universal ideals must undoubtable accept the category of difference in order to support and promote values of subjectivities.